Crisis Leadership in Small Businesses : Examining the Decision-Making Processes and Temporal Framework for Business Recovery - Sirwan, Lawen; Petrů, Jaroslav; Pauknerová, Daniela, 1970-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
This thesis examines the decision-making processes of leaders during crises, with a specific focus on their successful recovery strategies. The primary objective is to develop a practical guidebook for small business leaders on navigating crises, such as the COVID-19 pandemic. The research utilizes a mixed-methods approach, combining qualitative interviews with leaders who successfully guided their businesses through COVID-19 and quantitative surveys to explore the relationship between employee involvement in the success of these businesses. The study gathers primary data from two countries, the Czech Republic and Iraq, to analyze the impact of COVID-19 on businesses, the leadership qualities essential for recovery, the time required for recovery, and the distinct stages involved in the process. The quantitative component investigates the influence of employees on organizational recovery, revealing important connections between leadership behaviors and employee engagement. The findings highlight the critical role of leadership qualities such as communication, empathy, and flexibility in crisis recovery. Quantitative analysis further demonstrates significant relationships between employee recognition by leaders, employee trust in leadership, and employee involvement in decision-making processes during crises recovery. These insights provide valuable guidance for small business leaders to effectively lead their organizations through challenging times.
Vedoucí práce: Jaroslav Petrů
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses